Revitalization Strategies In Human Resource Development - Djatola, Hariyanto R; Hilal, Nur (BALANCE: Economic, Business, Management and Accounting Journal, 2025)
This research aims to analyze and identify practical human resource (HR) development strategies to improve quality and productivity. The main focus of this study is to formulate strategic approaches that management can use to enhance employees' competencies, skills, and motivation, aligning them with organizational needs and changes in the business environment. The research method used is descriptive qualitative research, which generates descriptive data from observable individual behaviors expressed in written or spoken language. Data collection is carried out through informant interviews or direct observation. Since the study employs a qualitative design, the researcher cannot make short-term assumptions about the observed events. The findings reveal several threats and weaknesses, with a low score of 2.23, such as intense labor market competition and resource constraints in certain areas. The strength-threats analysis shows a score of 3.49, indicating that these challenges can be addressed by optimizing existing strengths and reinforcing the organization’s position through a holistic and sustainable HR development strategy. The implications of this research suggest that implementing strategies based on internal strengths will strengthen the organization's position in managing resource limitations and external threats. The recommendation is to enhance synergy between the HR department and other organizational units to create more integrated and adaptive HR development policies